A new way to regulate inflammation: selective autophagic degradation of IKKγ mediated by ANGPTL8 - Yu Zhang; Ling Zheng; Kun Huang (Cell Stress, 2018)
Bronchopulmonary dysplasia (BPD) is the most common chronic lung disease in infants with lifelong pulmonary and neurodevelopmental consequences. The pathogenesis of BPD is contributed by genetic and environmental factors; among the latter, a critical contributor is exposure of the developing lung to hyperoxia. We have recently reported (Nat Comm 8:1173) that hyperoxia exposure in our in vitro and in vivo modeling systems of hyperoxia-induced lung injury (HALI) and BPD leads to an upregulation of the microRNA (miR) 34a. Utilizing genetic loss- and gain- of function strategies, we show that miR34a inhibition ameliorates the pulmonary phenotype of BPD (including BPD-associated pulmonary hypertension), at least in part, via one of the downstream targets of miR34a, namely Angiopoietin1/Tie 2 signaling. In addition, we demonstrate translational clinical significance of our findings by showing increased miR34a and decreased Ang1 expression in 3 independent cohorts of human lung samples.